The basics of the innovative tendency and its relationship to the family and educational climate of innovators (Journal of the College of Basic Education, 2023)
The development achieved by human civilization throughout its long history is indebted to human beings who played a major and effective role in it because of their innovative capabilities that they employed in their positive bids in various aspects of social, scientific and artistic life at its various levels, and that the aspirations expected in it depend on the activity of innovators after creating the conditions for organizing activities and accelerate the maturity of their preparations.This image, in its ancient and modern form, began to be clear and obvious to the developing peoples today, just as it began to develop among the developed peoples yesterday. Therefore, caring for it has become an imposed duty required by the development of man's preparations and capabilities to the maximum extent possible through which his stability on the one hand and the service of his society on the other hand.It has become clear that interest in the human element, reliance on it, and acceleration of its growth are at the forefront of the guarantees on which the progress and renaissance of peoples depend, and the continuation of their path in this progress. Education has become a means for these societies to achieve this. And if it is absent from some the site of innovation and creativity as a main goal among the educational goals, then it is known and clear, as it included the tenth educational goal (the goal of originality and renewal), and the fifth paragraph stipulated (development of creativity and innovation in renewing life and improving its quality at the level of individuals and groups. Renewal stems from the nature of the nation in areas of science, literature and the arts).So now the problem is no longer one of interest or lack of interest in innovative activity, and it is not a problem of clarifying its importance in the present and future life. Rather, it is the problem of increasing the scientific vision of its nature and increasing the experience practically and empirically in the possibility of increasing the innovative energy of individuals and groups and selecting the best methods and activities in accelerating it and ensuring better results in the life of society through it.This bright, optimistic future image is relatable. Based on the current reality of my life and traditional educational patterns through which innovation and creativity do not grow easily. Therefore, it is necessary to look at the aspects of social life in general and the family in particular. It is also necessary to tour the fields of education in general and the field of school in particular to find out the role of each of them in innovative education with a diagnosis of the existing problems in it. And the possibility of replacing them with positive sources in the actual structure of the students and their creative activity. Educators have sought since time immemorial to try to discover the creators and those with the ability to innovate in the early stages of their lives, so we see them focus on children in schools in the early learning stages and try to highlight these creative capabilities and innovative talents To the public through the media and independent community institutions or individuals or companies in vigorous attempts to sponsor the owners of these talents in most countries of the world, but that many countries of the world have begun to establish schools for the creative, distinguished, gifted and innovative and gather in them those who believe in the advantages of creativity and innovation (Bahri and Janabi, P. 5: 2007).The existing research is a modest attempt in this field, perhaps it constitutes a letter of a word or a word of a sentence or a phrase in a page that calls for increasing work on developing the capabilities of the Arab individual to serve his nation and humanity as a whole.